Innovation and entrepreneurial small firms in the tourism sector - Savelli, Elisabetta; Murmura, Federica; Anton Clavé, Salvador (Piccola Impresa / Small Business, 2025)
Purpose. This editorial introduces and contextualizes the thematic framework underpinning the Special Issue on innovation and entrepreneurial small firms in the tourism sector. It examines how entrepreneurship, sustainability transitions, digital transformation, youth engagement, and circular models are reshaping tourism ecosystems, with a specific focus on the role of small firms and peripheral territories. Design/methodology/approach. The editorial summarizes and discusses the five contributions included in the Special Issue, highlighting their collective insights into eco-entrepreneurship, sustainability communication, circular economy adoption, youth-driven development, and the influence of founders’ educational backgrounds on intellectual capital and business models. Findings. The contributions show how innovation in tourism SMEs is a relational and context-dependent phenomenon emerging from the interplay of entrepreneurial values, human capital, territorial identity, and institutional frameworks. Practical and social implications. The findings underscore key levers for sustainable and inclusive tourism growth, including improved governance, communication capacity, territorial networking, youth empowerment, and cross-disciplinary competencies. Originality of the study. The editorial frames innovation in small tourism firms as a multi-actor, ecosystem-based and place-sensitive process.